2018
DOI: 10.1093/jas/sky360
|View full text |Cite
|
Sign up to set email alerts
|

Prepartum fatty acid supplementation in sheep. III. Effect of eicosapentaenoic acid and docosahexaenoic acid during finishing on performance, hypothalamus gene expression, and muscle fatty acids composition in lambs1

Abstract: The objectives of this study were to evaluate the effect of feeding an enriched diet with eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) to finishing lambs born from ewes supplemented either with or without EPA and DHA during late gestation on productive performance, muscle fatty acid (FA), and hypothalamus mRNA concentration of metabolic genes and hormone receptors. Lambs born from dams fed during the last 50 d of gestation either with a control diet containing 0.39% Ca salts of palmitic fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 39 publications
(54 reference statements)
6
30
3
Order By: Relevance
“…Jones et al [ 10 ] reported an increased in fetal and placental growth after omega-3 PUFA supplementation during late gestation in rats. In accordance with Jones et al [ 10 ], Carranza Martin et al [ 28 ] reported an increase in birth BW in lambs born from dams supplemented with 0.39% Ca salts of n-3 PUFA during the last 50 days of gestation. Likewise, a heavier birth weight was associated with in late gestation RPM supplementation in Holstein cows, suggesting that maternal supply of Met during late pregnancy enhanced in utero growth [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Jones et al [ 10 ] reported an increased in fetal and placental growth after omega-3 PUFA supplementation during late gestation in rats. In accordance with Jones et al [ 10 ], Carranza Martin et al [ 28 ] reported an increase in birth BW in lambs born from dams supplemented with 0.39% Ca salts of n-3 PUFA during the last 50 days of gestation. Likewise, a heavier birth weight was associated with in late gestation RPM supplementation in Holstein cows, suggesting that maternal supply of Met during late pregnancy enhanced in utero growth [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…Supplementation with omega-3 PUFA or Met has beneficial effects on development and growth of the offspring, and supplementation with one or the other has showed to modify the expression of immune mediators, enzymes involved in DNA methylation, and increased growth, but the effects of supplementation with both nutrients on fetus growth, gene expression of cytokines in the NF-κB pathway, enzymes present in the methionine cycle, DNA methylation, and in the RvD1 omega-3 PUFA metabolic pathway, as well as on global DNA methylation of fetal tissues, have not been studied. According to previous studies [ 4 , 11 , 28 ], we expect that fetus growth from dams supplemented with these two nutrients will be associated with an increase in the mRNA expression of the enzymes that participates in DNA methylation (DNMT), Met cycle, and RvD1 metabolic pathway after PUFA supplementation. We assume that PUFA supplementation would modified the expression of DNMT enzymes and Met supplementation will increase methyl donors, thus increasing DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations